2013
DOI: 10.1017/s0022215113000856
|View full text |Cite
|
Sign up to set email alerts
|

Are UK otorhinolaryngologists maintaining their research output?

Abstract: These results are encouraging as they refute the fall in UK research output observed by other authors. In the face of growing challenges, it is important to maintain published output so that the fate that has befallen other specialties is not mirrored within UK otorhinolaryngology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…There have been growing concerns that a combination of increasing budgetary constraints, changes to postgraduate training and seismic organisational restructuring within the National Health Service have taken its toll on research throughput . The overall proportion of publications in the top 10 otolaryngology journals (based on impact factor) accredited to UK departments have remained below 4% for a decade since 2000 . Although the authors reported an increased number of published articles and concluded that the results were encouraging as it refuted the fall in UK research output observed by others, it must be remembered that this growth is from a low base.…”
Section: Discussionmentioning
confidence: 97%
“…There have been growing concerns that a combination of increasing budgetary constraints, changes to postgraduate training and seismic organisational restructuring within the National Health Service have taken its toll on research throughput . The overall proportion of publications in the top 10 otolaryngology journals (based on impact factor) accredited to UK departments have remained below 4% for a decade since 2000 . Although the authors reported an increased number of published articles and concluded that the results were encouraging as it refuted the fall in UK research output observed by others, it must be remembered that this growth is from a low base.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of cuts to research funding in the United Kingdom further supports this finding [2,4]. Increasing service demands have also been implicated in decreasing research output [2].…”
Section: Discussionmentioning
confidence: 60%
“…By 2012 the percentage of Canadian papers with 3 or more authors (90%) was comparable to that of non-Canadian papers (89.2%). There was a significant increase in multi-authorship in Canadian authored papers from 2008 to 2012 (χ 2 [trend], p = .014).…”
Section: Number Of Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Finally, Kulkarni and colleagues analyse research output from UK otorhinolaryngologists during the period 2000-2010. 8 The perception of many is that research output has fallen due to many factors, such as funding restriction, difficulty obtaining project approval and changes in training programmes. It is encouraging, therefore, that these authors have found that on a worldwide basis the research output from the UK and Ireland grew by 22.8 per cent during the 10-year study period.…”
Section: -4mentioning
confidence: 99%